Efficient synthesis of varenicline - Pasikanti, Srinivas; Reddy, D. Srinivasa; Venkatesham, B.; Dubey, P. K.; Iqbal, Javed; Das, Parthasarathi (Tetrahedron Letters, 2010)
Synthesis of varenicline the antismoking drug has been achieved in six steps with 10% overall yield. A Diels-Alder reaction, oxidative cleavage of an olefin and reductive amination remain as key steps in the synthesis (C) 2009 Elsevier Ltd. All rights reserved.